Toxicidade celular e ação do EGCG sobre biofilme simples e misto de microrganismos de interesse endodôntico - Assumpção, Thainara de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
One of the main causes of failure in endodontic therapy is the persistence of microbial infection even after chemical-mechanical preparation and application of intracanal medication. Many authors have explored the use of herbal medicines in order to obtain new compounds that have therapeutic properties without causing microbial resistance. Among these are the flavonoids, natural phenolic compounds which have different properties such as antimicrobial, antioxidant, osteogenic and antiosteoclastogenic. One of these flavonoid that has received attention in the literature is epigallocatechin-3-gallate (EGCG), which has also shown effect against oral pathogens. Thus, the objectives of this study were to evaluate the antimicrobial activity of EGCG on planktonic culture and simple or dual-species biofilms of microorganisms resistant to endodontic treatment, as well as evaluate its toxicity on culture of fibroblasts. Tests were performed in the planktonic culture to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of EGCG against Enterococcus faecalis, Streptococcus mutans, Actinomyces israelii, Pseudomonas aeruginosa and Fusobacterium nucleatum and also biofilm assays with some of these microorganisms in combination with E. faecalis. In addition, the cytotoxicity of EGCG was determined on L-929 fibroblast line after 24 h exposure using the MTT assay. Data were statistically analyzed using ANOVA/Tukey tests, considering p<0.05. The results showed that EGCG showed a bactericidal effect against all the evaluated species, with values of CBM varying between 0.03 and 2 mg/mL. except by P. aeruginosa. The elimination of the viable cells from the single biofilm of S. mutans and F. nucleatum and reduction of the biofilms of E. faecalis and A. israelii were observed after treatment of the biofilms with EGCG. It has also...

Uma das principais causas do insucesso nas terapias endodônticas é a persistência da infecção microbiana mesmo após o preparo biomecânico e o uso de medicação intracanal. Muitos autores tem explorado o uso de fitoterápicos, visando obter novos compostos que apresentem propriedades terapêuticas. Dentre esses, estão os flavonoides, compostos fenólicos naturais que apresentam diversas propriedades, como antimicrobiana, antioxidante, osteogênica e antiosteoclastogênica. Um desses flavonoides que vem recebendo destaque na literatura é o epigallocatechin-3-gallate (EGCG), que também tem mostrado efeito contra patógenos bucais. Sendo assim, os objetivos do presente estudo foram avaliar a atividade antimicrobiana do flavonoide EGCG sobre cultura planctônica e biofilme simples ou dual-espécie de microrganismos de interesse endodôntico, além de avaliar sua toxicidade em cultura de fibroblastos. Foram realizados ensaios em cultura planctônica para determinar a concentração inibitória mínima (CIM) e concentração bactericida mínima (CBM) do EGCG contra Enterococcus faecalis, Streptococcus mutans, Actinomyces israelii, Pseudomonas aeruginosa e Fusobacterium nucleatum e também ensaios de biofilme alguns desses microrganismos combinados com E. faecalis. Além disso, a citotoxicidade do EGCG foi determinada sobre fibroblastos da linhagem L-929, após exposição por 24h, utilizando o ensaio de methyltetrazolium (MTT). Os dados foram analisados estatisticamente, utilizando os testes de ANOVA/Tukey, considerando p<0,05. Os resultados mostraram que EGCG apresentou efeito bactericida contra todas as espécies avaliadas, com valores de CBM variando entre 0,03 e 2 mg/mL, com exceção para P. aeruginosa >2 mg/mL. A eliminação das células viáveis do biofilme simples de S. mutans e F. nucleatum e redução significante...
Keywords: Flavonoides; Biofilmes; Anti-infecciosos; Flavonoids